2005
DOI: 10.1136/vr.156.13.408
|View full text |Cite
|
Sign up to set email alerts
|

Serosurvey of Aujeszky’s disease virus infection in European wild boar in Spain

Abstract: Serum samples from 693 hunted wild boar (Sus scrofa) were analysed by means of a blocking ELISA technique, and the mean (se) prevalence of antibodies to Aujeszky's disease virus was 44 (4) per cent. All the seropositive wild boar were from south central Spain, except for one from central Spain, close to the main positive area. In this area, where large game species are increasingly managed for hunting, the seroprevalence was affected by the type of management. More intensively managed populations had a higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 16 publications
6
64
1
Order By: Relevance
“…This causes serious concerns regarding disease control, since different local populations are well above the threshold that allows infectious diseases to be maintained without introductions from other wild or domestic sources. This may explain, for example, the high seroprevalence of ADV in central and southern Spanish wild boar populations [7], and the fact that TB has been circulating among wild ungulates in fenced estates for over 20 years without any contact with domestic livestock [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This causes serious concerns regarding disease control, since different local populations are well above the threshold that allows infectious diseases to be maintained without introductions from other wild or domestic sources. This may explain, for example, the high seroprevalence of ADV in central and southern Spanish wild boar populations [7], and the fact that TB has been circulating among wild ungulates in fenced estates for over 20 years without any contact with domestic livestock [8].…”
Section: Discussionmentioning
confidence: 99%
“…The seroprevalence of ADV has also been previously described for our study area [7]. In contrast to PCV2, ADV remains infectious within the host for life, and transmission can also occur venereally or via the consumption of carcasses or hunting remains [37].…”
Section: Disease Prevalencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneously, over the last few decades an increase of the wild boar population, acting as possible PrV transmitters, has been recorded in most European countries. Serological surveys and virological screenings have shown that in many regions of Europe the prevalence of PrV in populations of wild boar is higher than expected (Vicente et al, 2005;Müller et al, 2011;Wodak, 2011;Boadella et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These changes in wildlife management have already raised concerns regarding the control of infectious and parasitic diseases [11,38,39]. In this context, our aims were the following: (a) to assess the occurrence and prevalence of TB-like lesions (TBL) through a nationwide survey of red deer and wild boar, and through an exploratory analysis, (b) to describe epidemiological patterns and (c) to investigate the relationships between the presence of TBL in both species.…”
Section: Introductionmentioning
confidence: 99%